An evaluation of bioenergy industry sustainability impacts on forest degradation: evidence from European Union economies - Mohd Alsaleh; Abdul-Rahim, A. S. (Springer, 2022)
The bioenergy industry is a proven option to replace fossil fuels in the heat supply and partly in the transport sector and generation of electricity. The study aims to investigate the empirical model of whether bioenergy use and institutional quality increase forest destruction in the European Union 28 countries covering the period 1990–2018, using the pooled ordinary least squares (pooled OLS), fixed effect, random effect, and least square dummy variable corrected. The findings indicate that bioenergy use within an institutional framework significantly contributes to a reduction in forest degradation regardless of the development status of countries in the region. This shows that efficient institutions and governments can significantly contribute to reducing forest degradation in the region especially in developed countries. Thus, policy-makers should stimulate the sustainability criteria of bioenergy application end-uses, intensify the quality of institutions, and ensure bioenergy use under effective governance.